Evaluation of visual electrophysiology and retinal nerve fiber layer analysis in nonarteritic anterior ischaemic optic neuropathy patients - Muhammed, Julieana (2015)
INTRODUCTION Nonarteritic anterior ischaemic optic neuropathy (NAION) is a disease among elderly more than 50 years old that leading to blindness. Assessment and monitoring of this disease is essential in order to evaluate the structural and functional damage. Visual electrophysiology tests (pattern electroretinogram (PERG) and pattern visual evoked potential (PVEP)) able to detect axonal degeneration and functional impairment of retina ganglion cells (RGC) in patient with NAION. Assessment of Retinal Nerve Fiber Layer (RNFL) with Optical Coherence Tomography (OCT) provides 3-Dimensional image of RNFL, objectively evaluate the RNFL thickness and detection of structural damage. It compliments the existing standard structural and functional test. OBJECTIVE To evaluate visual electrophysiology response and retina nerve fibers layer (RNFL) thickness in NAION. The correlation between visual electrophysiology with RNFL thickness were also evaluated. MATERIALS AND METHODS A comparative cross sectional study was conducted in Hospital Universiti Sains Malaysia involving 42 samples of NAION patients and controls. A complete ocular examination was done to confirm the diagnosis of NAION. Evaluation of structural changes of RNFL was conducted using Cirrus SD-OCT (Carl Zeiss Meditec Inc, USA) with good signal strength (≥ 6/10). PERG (0.8º checks size) and PVEP (0.25º checks size) was conducted by a trained technician. Mann-Whitney test and Spearman’s correlation coefficient analysis were used in statistical analysis. RESULTS There were statistically significant reduction in amplitudes and prolonged in latencies of PVEP in NAION patients (p<0.001). There were also significant reduction in magnitude of amplitude (p<0.001) and prolonged latency in PERG (p<0.001). There was also significant thinning of Mean RNFL thickness in NAION patients (p<0.001). No significant correlation between RNFL and latency and amplitudes of PVEP and PERG. CONCLUSION Visual electrophysiology tests and RNFL analysis has shown significant changes in NAION patients. This supports that PERG, PVEP and OCT are complimentary tests in assessment and monitoring structural and functional damage in NAION.